The Influence of Social Media for the Development of Da’wah and Nahdlatul Ulama Society Behavior - Avin Wimar Budyastomo (Lakpesdam PCNU Kota Salatiga, 2020)
The development of information technology is felt so rapidly. All fields have used information technology; both in medicine and exact science, and even now the religious field has used it. One of the advantages of information technology in the field of religion is the emergence of sites that contain da'wah or religious promotions. This is far different from the time of Prophet Muhammad SAW when delivering da'wah for the first time. He delivered da’wah stealthily and took very long time, but the existence of social media turned into open and transparent media and saved time and energy. In addition, social media can also be used as a means to change the behavior and lifestyle of society, one of which is the nature of dependence on social media, and fashion changes very quickly.